1991
DOI: 10.1111/j.1432-1033.1991.tb16300.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase activity in the interaction ofN‐formyl‐l‐methionyl‐l‐leucyl‐l‐phenylalanine with human polymorphonuclear leukocytes

Abstract: Human polymorphonuclear leukocytes (PMN) hydrolyze the synthetic chemoattractant N-formyl-Lmethionly-L-leucyl-L-phenylalanine (fMet-Leu-Phe) at nanomolar concentrations in an autocatalytic-like manner that deviates from classical Michaelis-Menten kinetics [Yuli, I. & Snyderman, R. (1986) J . B i d . Chem. ,761,4902-49081. By using inhibitors of distinct classes of endoproteases, this particular Wet-Leu-Phe degradation was attributed exclusively to an exoplasmic metalloendoprotease that matches the ubiquitous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Previous studies have observed the expression of NEP on the surface of PMN [38,39]. In addition, the NEP activity was higher in the LPS-treated mice, in which the recruitment of PMN into the air-space was increased.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have observed the expression of NEP on the surface of PMN [38,39]. In addition, the NEP activity was higher in the LPS-treated mice, in which the recruitment of PMN into the air-space was increased.…”
Section: Discussionmentioning
confidence: 71%